Liszt and the issue of so called Gypsy music - Piotrowska, Anna G. (Interdisciplinary Studies in Musicology, 2018)
The article attempts to shed light on Liszt’s connections with so called Gypsy music, with particular emphasis on the sources and manifestations of the composer’s interest in the subject. The paper also shows the effects of Liszt’s thought on his academic successors. Liszt’s fascination with Gypsy music and culture is discussed by outlining his childhood memories as well as indicating numerous personal contacts he had with renowned Gypsy musicians. The author of the paper also links Liszt’s enchantment with Gypsy culture with his readiness to identify his travelling virtuoso status with that of a Gypsy-wanderer. Special attention in the article is put on Liszt’s book Des Bohemiens et de leur musique en Hongrie (1859). The author of the article claims that Liszt’s cosmopolitanism may be a key factor while explaining the composer’s predilection to Gypsy culture and music. While focusing on the reception of Liszt’s views on so called Gypsy music by the posterity Bartok’s interpretation of Liszt’s ideas is reminded. Discussed are also their repercussions in the second half of the twentieth century and early twenty first century.